2016
DOI: 10.1177/0269215516675906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the FIFA 11 training program on injury prevention and performance in football players: a systematic review and meta-analysis

Abstract: FIFA 11 can be considered as a tool to reduce the risk of injury. It may improve dynamic balance and agility and can be considered for inclusion in the training of football players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 29 publications
0
41
1
2
Order By: Relevance
“…Three main target groups of RRI prevention can be exposed from this study: males, overweight runners (BMI≥25 kg/m2), and previously injured runners. Lessons learned from anterior cruciate injuries and hamstring muscle tears have clearly shown that both can be reduced with dedicated preventive exercise ( 19 , 20 ). Both injuries are quite easy to detect after an abrupt injury, as sportsmen are unable to continue with sports without medical help.…”
Section: Discussionmentioning
confidence: 99%
“…Three main target groups of RRI prevention can be exposed from this study: males, overweight runners (BMI≥25 kg/m2), and previously injured runners. Lessons learned from anterior cruciate injuries and hamstring muscle tears have clearly shown that both can be reduced with dedicated preventive exercise ( 19 , 20 ). Both injuries are quite easy to detect after an abrupt injury, as sportsmen are unable to continue with sports without medical help.…”
Section: Discussionmentioning
confidence: 99%
“…Since court‐based athletes frequently engage in change in direction cutting actions within their sport, they may have been less responsive to positively adapt to such movements within the training intervention . It is also important to note, a meta‐analysis conducted by Gomes Neto et al who analyzed eleven FIFA 11+ studies, including 4700 participants. The analysis indicated an overall significant improvement in agility performance following engagement in the FIFA 11+ program .…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note, a meta‐analysis conducted by Gomes Neto et al who analyzed eleven FIFA 11+ studies, including 4700 participants. The analysis indicated an overall significant improvement in agility performance following engagement in the FIFA 11+ program . This may be indicative of the benefit of longitudinal implementation of the FIFA 11+ on agility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sports managers in the field of sports play just the same role played by business managers; they determine the performance of the organization off and on the playing field (Galariotis, Germain, & Zopounidis, 2018). In football, according to Gomes, at al., (2017), performance is mainly based on the quality of the players. For example, in the 2017/2018 season, Manchester City used as much as €213.8 million in buying quality players from the different clubs in Europe.…”
Section: Sport Management Educationmentioning
confidence: 99%